Traditional Customs from Otavalo to Improve Vocabulary in NinthGrade Students at Jacinto Collahuazo High School - Panamá Santillán, Cinthya Soledad (2025)
Propose traditional customs from Otavalo to improve vocabulary in ninth-grade students at Jacinto Collahuazo High School.